Методологические разработки А. В. Сурилова и проблема совершенствования методологии юридической науки - Бехруз, Хашматулла Набієвич; Behruz, Hashmatulla (Одеса : Юрид. л-ра, 2012)
The article examines the legacy of the famous theorist of law Aleksey Vasilyevich Surilov. Particular attention is paid to the value of his methodological developments to improve the methodology of jurisprudence, that is reflected in the works of a scientist, published in the Soviet's period, and influenced the development of post-Soviet theoretical jurisprudence.
Бехруз X. Методологические разработки А. В. Сурилова и проблема совершенствования методологии юридической науки / X. Бехруз // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 113-118.
Keywords: А. В. Сурилов; методология юридической науки; совершенствование методологии; методы; методологические принципы; развитие юридической науки; О. В. Сурілов; методологія юридичної науки; удосконалення методології; методи; методологічні принципи; розвиток юридичної науки; A.V. Surilov; the methodology of jurisprudence; the improvement the methodology; methods; methodological principles; the development of legal science